The Omnipaper metadata RDF/XML prototype implementation - Pereira, T. (2003)
Omnipaper (Smart Access to European Newspapers, IST-2001-32174) is a project from the European Commission IST program (Information Society Technologies) that investigates and proposes ways for access to different types of distributed information sources. This article intends to introduce the technology Resource Description Framework - RDF, developed by W3C for the Web based on metadata, and its practical use in the Omnipaper project, which the authors are involved. We intend to achieve the implementation of a prototype that enables users (professional journalists and occasional users) to have simultaneous and structured access to the articles of a large number of digital European news providers. Omnipaper is not a project about digitalization of news, but about bringing digitized news originating from various sources (and in various formats) together. In this article will be described the procedure implemented in the description of our newspaper articles using the RDF technology, followed by a elaborated description on the manipulation process and treatment of the information structured in RDF, through the RDF Gateway.